2018
DOI: 10.12669/pjms.346.16140
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms underlying visual pareidolia processing: An fMRI study

Abstract: Objectives:Pareidolia is the interpretation of previously unseen and unrelated objects as familiar due to previous learning. The present study aimed to determine the specific brain areas that exhibited activation during real-face and face-pareidolia processing.Methods:Functional Magnetic Resonance Imaging (fMRI) scans were performed on 20 healthy subjects under real-face and face-pareidolia conditions in National Magnetic Resonance Research Center (UMRAM), Ankara, Turkey from April 2016 to January 2017. FSL so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…us, we postulate that the evoked larger N170 response in PD patients during face-pareidolia perception may result from altered interaction between topdown and bottom-up brain region modulation from higher frontal cortical areas due to the damage of dopaminergic pathways in the disease. Our findings support the results of Akdeniz's and colleagues' study which demonstrated that fMRI scans were performed on 20 healthy subjects under real-face and face-pareidolia conditions [17]. ey found that face pareidolia requires interaction between top-down and bottom-up brain regions including the fusiform face area and frontal and occipitotemporal areas.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…us, we postulate that the evoked larger N170 response in PD patients during face-pareidolia perception may result from altered interaction between topdown and bottom-up brain region modulation from higher frontal cortical areas due to the damage of dopaminergic pathways in the disease. Our findings support the results of Akdeniz's and colleagues' study which demonstrated that fMRI scans were performed on 20 healthy subjects under real-face and face-pareidolia conditions [17]. ey found that face pareidolia requires interaction between top-down and bottom-up brain regions including the fusiform face area and frontal and occipitotemporal areas.…”
Section: Discussionsupporting
confidence: 92%
“…Pareidolia, are complex visual hallucination-like illusions involving ambiguous forms that is the interpretation of previously unseen and unrelated objects as familiar due to previous learning [17]. Patients with PD without dementia have been reported to be present in about visual hallucinations 10% [18][19][20] and visual illusion in 6-19% [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…2009 ). Whole-brain fMRI analysis indicates that in a sample of predominately female TD adults, perception of faces and face-like images elicits similar activation in the occipital cortices, FFA, and inferior temporal areas ( Akdeniz et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such preference in species with no parental care advocates the existence of a general mechanism to detect animacy in the natural environment [12]. Brain imaging such as functional magnetic resonance imaging, fMRI [13,14], magnetoencephalography, MEG [15], and electroencephalography, EEG [16][17][18][19] reveal that real faces and face-like nonface images activate similar occipito-temporal brain clusters with a hub in the fusiform face area, FFA (for review, see [20,21]). Face impression in such images usually arises spontaneously without any efforts.…”
Section: Introductionmentioning
confidence: 99%